Analysis of the Effect of FDR, BOPO, ROA and Inflation on Non-Performing Financing at Islamic Rural Banks in Java for the 2020-2023 Period - Natasya, Putri Aulia; Ruhadi, Ruhadi (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
This study analyzes the effect of financial performance ratios and macroeconomic indicators on the asset quality of Sharia Rural Banks (BPRS) in Java, using panel data from 78 BPRS for the period 2020–2023 selected through purposive sampling. Financial performance ratios are measured using FDR, BOPO, and ROA, while macroeconomic indicators are represented by the inflation rate. Asset quality is proxied by Non-Performing Financing (NPF). The analysis was conducted using panel data regression methods. The results of the study indicate that FDR, BOPO, ROA, and inflation simultaneously have a significant effect on NPF. However, only FDR and ROA have a significant positive effect on NPF, while BOPO and inflation do not show a significant effect.